Pilihan Rasional Masyarakat Menggunakan Angkutan Umum Antar Kota Dalam Provinsi (Superben) - Sitompul, Yulu Yanti; Risdayati, Risdayati (Peneliti.net, 2025)
Transportation is a means of distributing people's needs which functions to move or move goods or people from one place to another with the help of machine or human power. Therefore, it is important to consider people's actions in choosing which mode of transportation to support all their mobility activities. The aim of this research is to find out the things behind people's decisions to use Inter-City Within Province public transport (superben) using James Coleman's Rational Choice Theory approach. The subjects selected in this research included five main informants, two key informants, and one additional informant. The research subjects were determined using accidental sampling techniques. Data collection techniques used participant observation, unstructured interviews, and documentation. This research uses a descriptive qualitative research method with the Miles and Huberman model. The results of this research show that users as actors have an important role in determining decisions regarding the actions they choose, where this is influenced by resources, both internal and external resources. Internal resources include physical capabilities and financial capabilities. Meanwhile, external resources include the availability of public transportation every day and operating once an hour, comparison of travel costs, and ease of access using public transportation. Apart from that, the actor's intention to act is to choose due to the time factor, the availability of transportation modes, the need to always use public transportation, and the factor of saving costs